One-pot synthesis of bioactive cyclopentenones from α-linolenic acid and docosahexaenoic acid. Issue 7 (1st April 2018) - Maynard, Daniel; Müller, Sara Mareike; Hahmeier, Monika; Löwe, Jana; Feussner, Ivo; Gröger, Harald; Viehhauser, Andrea; Dietz, Karl-Josef
Graphical abstract: Abstract: Oxidation products of the poly-unsaturated fatty acids (PUFAs) arachidonic acid, α-linolenic acid and docosahexaenoic acid are bioactive in plants and animals as shown for the cyclopentenones prostaglandin 15d-PGJ2 and PGA2, cis -(+)-12-oxophytodienoic acid (12-OPDA), and 14-A-4 neuroprostane. In this study an inexpensive and simple enzymatic multi-step one-pot synthesis is presented for 12-OPDA, which is derived from α-linolenic acid, and the analogous docosahexaenoic acid (DHA)-derived cyclopentenone [(4 Z, 7 Z, 10 Z )-12-[[-(1 S, 5 S )-4-oxo-5-(2 Z )-pent-2-en-1yl]-cyclopent-2-en-1yl] dodeca-4, 7, 10-trienoic acid, OCPD]. The three enzymes utilized in this multi-step cascade were crude soybean lipoxygenase or a recombinant lipoxygenase, allene oxide synthase and allene oxide cyclase from Arabidopsis thaliana . The DHA-derived 12-OPDA analog OCPD is predicted to have medicinal potential and signaling properties in planta . With OCPD in hand, it is shown that this compound interacts with chloroplast cyclophilin 20-3 and can be metabolized by 12-oxophytodienoic acid reductase (OPR3) which is an enzyme relevant for substrate bioactivity modulation in planta .